A REPORT ABOUT INTIMATE PARTNER VIOLENCE IN SOUTHERN AND WESTERN RWANDA - Immaculée Mukashema (International Journal of Child, Youth & Family Studies, 2018)
The present paper reports on intimate partner violence (IPV) in 3 districts of Southern Province and Western Province in Rwanda. Qualitative data were obtained via 3 focus group discussions conducted at the headquarters of each district, and 10 individual interviews with key informants, community leaders who worked in the districts. The types of IPV discussed were physical, economic, sexual, and psychological harassment. Community leaders stated that the women in their communities had no hesitation in reporting economic abuse and physical violence, but noted that the women needed support from other people to report sexual violence, and generally did not report psychological harassment, perhaps because they accepted it as the norm. They also noted that men generally did not report IPV and that the main victims of IPV in all its forms were children and women. The community leaders suggested a number of measures to reduce IPV: empowering females so that they are financially independent; educating and sensitizing family members about their responsibilities and community leaders about laws and human rights; educating all community members about gender equality and IPV, including premarital instruction; increasing access to services; putting in place a law that protects free unions by giving them legal status after a period of cohabitation; setting up a specific institution to deal with IPV; improving both support to the victims and follow-up of reported cases, along with instituting punitive responses to deter potential new perpetrators.